“Targeted Sequencing by Gene Synteny,” a New Strategy for Polyploid Species: Sequencing and Physical Structure of a Complex Sugarcane Region - Mancini, Melina C.; Cardoso-Silva, Claudio B.; Sforça, Danilo A.; Pereira de Souza, Anete (Frontiers in Plant Science, 2018)
Sugarcane exhibits a complex genome mainly due to its aneuploid nature and high ploidy level, and sequencing of its genome poses a great challenge. Closely related species with well-assembled and annotated genomes can be used to help assemble complex genomes. Here, a stable quantitative trait locus (QTL) related to sugar accumulation in sorghum was successfully transferred to the sugarcane genome. Gene sequences related to this QTL were identified in silico from sugarcane transcriptome data, and molecular markers based on these sequences were developed to select bacterial artificial chromosome (BAC) clones from the sugarcane variety SP80-3280. Sixty-eight BAC clones containing at least two gene sequences associated with the sorghum QTL were sequenced using Pacific Biosciences (PacBio) technology. Twenty BAC sequences were found to be related to the syntenic region, of which nine were sufficient to represent this region. The strategy we propose is called "targeted sequencing by gene synteny," which is a simpler approach to understanding the genome structure of complex genomic regions associated with traits of interest.